Article 101 TFEU and voluntary environmental agreements: more weight for environmental concerns? - Tuominen, Tiina (My University, 2021)
This Master’s thesis examines Article 101 TFEU and voluntary environmental agreements from the perspective of why and how environmental protection goals should play a role in the application of Article 101 TFEU. The central question is whether the importance of environmental protection or sustainable development has increased so that environmental factors should be allowed more weight in an Article 101 assessment. The background of the recently intensified debate is presented in the opening chapters, as are voluntary environmental agreements. After this, the more specific question of Article 101 TFEU and environmental factors is discussed. It is concluded that the approach to sustainability goals within the context of Article 101 is unclear and needs clarifying – and, possibly, a more permissive approach – from competition authorities, especially the European Commission. The current revising process of the Commission’s horizontal guidance would provide an opportunity for this, but other options are also discussed. This thesis analyzes the legislative framework and academic discussion regarding environmental law and competition law. On the EU level, the main sources – along with the relevant Treaty provisions –are the different Commission communications that are discussed often together with certain documents prepared by the OECD. The most important literary sources are the influential works of Suzanne Kingston, Nicolas de Sadeleer, Christopher Townley and Hans Vedder.

Tämä OTM-tutkielma käsittelee SEUT 101 artiklan ja vapaaehtoisten ympäristösopimusten suhdetta siitä näkökulmasta, miksi ja miten ympäristönsuojelulliset tekijät voivat tulla osaksi kilpailuoikeudellista arviointia, kun artiklaa 101 sovelletaan. Keskeistä tutkimuksessa on sen selvittäminen, ovatko ympäristönsuojelulliset ja kestävän kehityksen tavoitteet nousseet siinä määrin keskeiseen asemaan EU-oikeudessa, että niille tulisi antaa aiempaa vahvempi jalansija myös kilpailuoikeuden saralla. Tutkielman avauskappaleissa tarkastellaan aihepiiriä koskevan keskustelun taustoja – kiinnostus kilpailuoikeuden ja ympäristön suhteeseen on viime vuosina lisääntynyt entisestään. Tämän jälkeen paneudutaan lähemmin SEUT 101 artiklan ja ympäristönäkökulmien yhdistämiseen. Keskeisenä johtopäätöksenä on tarve tilanteen selkiyttämiselle ja kenties liikkumavaran lisäämiselle kilpailuoikeudellisessa analyysissa: kilpailuviranomaisten, erityisesti Euroopan komission, tulisi vahvistaa, miten ne suhtautuvat sopimuksiin, joilla on ympäristönsuojelullisia tavoitteita mutta jotka voivat olla kilpailuoikeudellisesti ongelmallisia. Komissio on parhaillaan arvioimassa 101 artiklaan liittyviä ohjeistuksiaan, minkä yhteydessä ympäristösopimusten käsittely olisi luontevaa. Muitakin mahdollisia ratkaisuja käsitellään lyhyesti. Tutkielmassa analysoidaan lainsäädäntöa ja akateemista keskustelua niin ympäristö- kuin kilpailuoikeudenkin alalta. EU:n tasolla primäärilähteiden lisäksi keskeisiä ovat komission kannanotot, joita peilataan usein OECD:n tuottamiin lähteisiin. Kirjallisuuslähteistä tärkeimpiä ovat Suzanne Kingstonin, Nicolas de Sadeleerin, Christopher Townleyn ja Hans Vedderin teokset.
Keywords: EU law, environmental law, competition law, cartel